Two new species of predatory biting midges of the genus Alluaudomyia from Europe and the Canary Islands (Diptera: Ceratopogonidae) - Szadziewski, Ryszard; Dominiak, Patrycja; Filatov, Serhii (Zootaxa, 2015)
Alluaudomyia canariensis Szadziewski & Dominiak sp. nov. from the Canary Islands and A. wyskokensis Szadziewski & Dominiak sp. nov. from Poland and Ukraine are described and illustrated. The genus Alluaudomyia is reported from the Canary Islands for the first time. The article is supplemented with a checklist and an identification key for the species so far recorded from Europe and the Canary Islands.